Meningkatkan Kemampuan Menghitung dengan Media Papan Hitung pada Siswa Kelas 2 SD Negeri Petir 2 Kota Tangerang - Weni, Mustika; Widiani, Uci; Zuliani, Rizki (Lembaga Yasin AlSys, 2023)
This study aims to develop a counting board learning media for grade 2 elementary schools. The research was conducted based on the basic facts in the field, it is known that the understanding of distribution is still low and there is a lack of supporting media for distribution. The type of research used is research that takes place in 3 stages. The research subjects were students of SD Negeri Petir 2 Tangerang City. The data collection technique used was a questionnaire which was assessed by giving questionnaires to students after using the counting board media. The results of this development research indicate that the developed learning media meets the good and feasible criteria so that it can be tested on grade 2 elementary school students. Based on the results of the total research sample, 90% of students received and felt the benefits of the division counting board learning media. The main benefit that students get is the division of the counting board which simplifies and speeds up the process of dividing arithmetic.